Influence of sport activity on hypertension - literature review - Fiega, Jakub; Lubaszka, Zuzanna; Michalska, Milena; Żurek, Urszula; Szewczyk, Dorota; Sikorska, Ewa (Journal of Education, Health and Sport, 2023)
One of the most widespread illnesses, hypertension can cause other cardiovascular conditions that shorten life expectancy and lower quality of life. Primary hypertension is the most typical type, and while there are some risk factors, we cannot determine what is the primary cause. We should first change our lifestyles before using medications. Sport activity is the strategy that has the most potential. Numerous researchers have attempted to evaluate its impact on hypertension control. They all concurred that engaging in almost any sport can aid in the management of hypertension. Other studies looked at the best sports to keep hypertension under control. They experimented with isometric exercises, tai chi, brisk walking, and aerobic exercise. Matching the appropriate sport to the level of hypertension can be important too. Athletes experience hypertension as well, despite the fact that exercise is beneficial for the condition. Because of anti-doping regulations, there are some restrictions on how they can be treated. In addition to exercise, other lifestyle changes are crucial in the treatment of hypertension. It involves changing one’s diet, attempting to lose weight, and avoiding stressful situations.